Tadakhkhulu al-Lughatu al-Umm fî Mahârati al-Kalâm bimarkazi al-Lughah al-'Arabiyah fî Ma'hadi al-'Inâyah Sumber Batu lilbanât Pegantenan Pamekasan - Khuluq, Muchsinul; Zulaikha, Siti (IAIN Madura, 2020)
This study covers 2 main problems, namely, what are the types of interventions Mother language in speaking skills at the Arabic Language Center of al-Inayah Putri Islamic Boarding School Sumber Batu Pegantenan Pamekasan and what are the factors that influence these interventions. This study uses a qualitative approach and data sources in this study came from the leadership of the cottage, the head of the Language center and several Arabic language center’s students of al-Inayah Putri Islamic Boarding School Sumber Batu Pegantenan Pamekasan. The method used in data collection is observation, interview and documentation. While the method used in analyzing data is a descriptive method. The results of this study indicate that there are 5 types of mother tongue interventions in speaking skills at the Arabic Language Center, namely phonetic interventions, morphological interventions, grammatical interventions, semantic interventions, and repetitive interventions. Of all the factors that researchers examined previously, most of the factors that often occur are censorship weakness, language position, initial use pressure, mastery of the first and second languages, the nature of interventions inherited earlier, and lack of vocabulary retention.